The Governmental and Enviromental Policies: Ecofeminism Resistance in the Wadon Wadas Civil Society Movement - Permatasari, Ane; Setiawan, Rendi Eko Budi (Politicon : Jurnal Ilmu Politik, 2024)
This research examines the role of ecofeminism in the Wadon Wadas movement's resistance to the Bener Dam project in Central Java, Indonesia. The study aims to highlight the gap between national development policies and their implementation, with a focus on environmental and gender issues in large-scale infrastructure projects. It also explores how the women's voices in the Wadon Wadas movement reflect broader injustices in the development process. A qualitative approach was used, involving direct interviews with Wadas Village residents and snowball sampling to gather insights from key informants. The data was analyzed using a social theory perspective to deepen the understanding of the findings. The results show that the Wadon Wadas movement, led by women, embodies ecofeminism by linking environmental protection with the fight against gender marginalization. The resistance against the Bener Dam project highlights a significant disconnect between national development goals and the real-life experiences of local communities, especially women. The study also reveals that the government's top-down approach, with limited community involvement, exacerbates tensions and fails to support sustainable development. The research suggests the need for more inclusive and adaptive policies, like the Dynamic Socio-Spatial approach, to better balance development with environmental and social justice.